Synthesis, Spectrochemical and Antimicrobial Activity of Heterocyclic α-Diketones, Dithiosemicarbazones and of 3,13-Diacylamino-7.9-diaryl-6-methyl- 4,14-dithia-1,2,8,11,12-pentazadispiro[4,4,4]tetradeca-2,12-dienes - Thilakam, R.; Jayamani, V.; Gayathiri, A.K.; Kalpana, R. (Asian Journal of Chemistry, 2011)
New heterocyclic α-diketones, their corresponding dithiosemicarbazones and dispiro compounds are prepared from 2,6-diaryl-4-piperidones. The synthesized compounds are characterized by spectral and analytical data. They are also screened for their antibacterial and antifungal activity against Staphylococcus aureus and Candida albicans.